(untitled) (The Peerian Journal, 2024)
The main goal of the research is to find solutions for the difficulties encountered while translating the poetry by Abu Al-Qasim Al-Shabi while accounting for pragmatic effects, cultural implications, and contextual considerations. The study makes use of samples from both qualitative and quantitative categories. The Gricean theory-based qualitative samples (2001) are based on the undergraduate M.A. students at Tikrit University, and the quantitative samples are randomly chosen. and use Newmark’s (1988) translational techniques while focusing on Abu Al-Qasim Al-Shabi’s poem "The Will of Life"